Morphological study of extrauterine length of the fallopian tube at different age group in Bangladeshi people - Ara, ZG; Islam, MS; Sultana, SZ; Mannan, S; Zaman, UK; Rahman, MM; Sen, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):37-40. The abstract of this article is available on the PubMed website